Attitudes, skills, and use of evidence-based practice: A cross-sectional survey of Swedish osteopaths. (December 2020) - Leach, Matthew J.; Shaw, Robert; Austin, Phil; Fryer, Gary; Thomson, Oliver P.; Adams, Jon; Skillgate, Eva; Sundberg, Tobias
Abstract: Background: Evidence-based practice (EBP) is integral to the provision of ethical, safe and high-quality health care. While osteopathy is an established and registered health profession in many countries, it is a developing, unregistered health profession in Sweden. This study explored the perceptions, skills, use, barriers and enablers of EBP among Swedish osteopaths. Methods: Osteopath members of the Swedish Osteopathic Association were invited by email to participate in an anonymous online survey - a Swedish-translated and pilot-tested version of the Evidence-Based Practice Attitude and Utilisation Survey. Data collection was conducted between January and March 2019. Results: Thirty-one per cent (78/249) of invited osteopaths responded to the survey. Respondents were largely supportive of EBP and most agreed or strongly agreed that EBP assisted clinical decision-making (84.7%), improved quality of patient care (83.3%), and was necessary in the practice of osteopathy (80.8%). Respondents typically reported moderate to moderate-high levels of EBP skills, whereas their level of engagement in EBP activities was variable and infrequent. The main reported barrier for EBP uptake was lack of clinical evidence in osteopathy. Workplace access to the internet and free online databases, and the ability to download full-text journal articles, were considered very useful enablers of EBP. Conclusions: The responding Swedish osteopaths appeared largely supportive of EBP, reported moderate to moderate-high levels of EBP skills but participated infrequently in EBP activities. Studies of interventions aimed at enhancing the skills and clinical use of EBP in osteopathy are warranted.